2012
DOI: 10.1371/journal.pone.0052056
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing ER Ca2+ Channel Function as an Early Preventative Strategy for Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative condition with no known cure. While current therapies target late-stage amyloid formation and cholinergic tone, to date, these strategies have proven ineffective at preventing disease progression. The reasons for this may be varied, and could reflect late intervention, or, that earlier pathogenic mechanisms have been overlooked and permitted to accelerate the disease process. One such example would include synaptic pathology, the disease component str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
133
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 47 publications
10
133
2
Order By: Relevance
“…Of note, the impairment of synaptic transmission caused by exogenously applied Ab42o has the same time window observed for alterations in neuronal Ca 2þ stores and a similar insensitivity to NMDAR blockade (Lee et al, 2013). As a whole, our data are fully consistent with a central role of aberrant ER Ca 2þ signaling in neuronal aging and cognitive decline (Berridge, 2014;Stutzmann and Mattson, 2011) and the use of ER Ca 2þ channel stabilizers in clinical AD trials (Chakroborty and Stutzmann, 2014;Chakroborty et al, 2012;Oules et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Of note, the impairment of synaptic transmission caused by exogenously applied Ab42o has the same time window observed for alterations in neuronal Ca 2þ stores and a similar insensitivity to NMDAR blockade (Lee et al, 2013). As a whole, our data are fully consistent with a central role of aberrant ER Ca 2þ signaling in neuronal aging and cognitive decline (Berridge, 2014;Stutzmann and Mattson, 2011) and the use of ER Ca 2þ channel stabilizers in clinical AD trials (Chakroborty and Stutzmann, 2014;Chakroborty et al, 2012;Oules et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Although increase in RyR3 transcript seems to have a neuroprotective effect (Supnet et al, 2010), it has been suggested that upregulation of RyR2, a finding common to several AD mouse models, could be an additional mechanism that contributes to synaptic failure and memory dysfunction in AD and in the aged brain (Bruno et al, 2012;Chakroborty et al, 2009;Kipanyula et al, 2012;Toescu and Verkhratsky, 2007). Consistently, dantrolene treatment is protective in APP mice and restores RyR2 levels (Chakroborty et al, 2012;Oules et al, 2012). At variance with rat hippocampal neurons (Paula-Lima et al, 2011), we did not observe significant increase in protein and transcript levels of RyR2 (and RyR3) following 1-hour treatment of mouse cortical neurons with Ab42o.…”
Section: Discussionmentioning
confidence: 96%
“…The protective effect of dantrolene treatment on WFS1-deficient cells suggests that dysregulated cellular calcium homeostasis plays a role in the disease progression of Wolfram syndrome. In addition, it has been shown that stabilizing ER calcium channel function could prevent the progression of neurodegeneration in a mouse model of Alzheimer's disease (48). Therefore, modulating calcium levels may be an effective way to treat Wolfram syndrome or other ER diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In December of 2012, Chakroborty et al 106 reported sub-chronically short-term (4 weeks) treatment of AD models with dantrolene. Using patch clamp recordings and 2-photon Ca 2+ imaging of hippocampal slices, the authors found that ER Ca 2+ signaling is fully normalized in dendritic compartments in dantrolene treated early and later-stage AD mice.…”
mentioning
confidence: 99%